Ectopic Thyroid in Stomach; a Case Report - Parvin Rajabi; Seyed Mehdi Eftekhari; Elham Rouhani; Omid Mirmosayyeb; Azar Baradaran (Iranian Society of Pathology, 2018)
An ectopic thyroid is a form of thyroid dysgenesis in which an entire or parts of the thyroid gland may be located in another part of the body than what is the usual place. The most frequent location is the base of tongue. Although most cases are asymptomatic, symptoms related to tumor size and its relationship with surrounding tissues, hormonal dysfunction and seldom malignancy may also occur. Any disease affecting the thyroid gland may involve the ectopic thyroid, including malignancy.